Frozen inactivated autograft replantation for bone and soft tissue sarcomas - Tian, Zhichao; Dong, Shuping; Yang, Yang; Qu, Guoxin; Liu, Guancong; Liu, Xu; Ma, Yue; Wang, Xin; Yao, Weitao (Frontiers in Oncology, 2024)
Background The frozen inactivation of autologous tumor bones using liquid nitrogen is an important surgical method for limb salvage in patients with sarcoma. At present, there are few research reports related to frozen inactivated autograft replantation. Methods In this study, we retrospectively collected the clinical data of patients with bone and soft tissue sarcoma treated with liquid nitrogen-frozen inactivated tumor bone replantation, and analyzed the safety and efficacy of this surgical method. The healing status of the frozen inactivated autografts was evaluated using the International Society of Limb Salvage (ISOLS) scoring system. Functional status of patients was assessed using the Musculoskeletal Tumor Society (MSTS) scale. Results This study included 43 patients. The average length of the bone defect after tumor resection is 16.9 cm (range 6.3–35.3 cm). Patients with autograft not including the knee joint surface had significantly better healing outcomes (ISOLS scores) (80.6% ± 15% vs 28.2% ± 4.9%, P<0.001) and limb function (MSTS score) (87% ± 11.6% vs 27.2% ± 4.4%, P<0.001) than patients with autografts including the knee joint surface. The healing time of the end of inactivated autografts near the metaphyseal was significantly shorter than that of the end far away from the metaphyseal (9.8 ± 6.3 months vs 14.9 ± 6.3 months, P=0.0149). One patient had local recurrence, one had an autograft infection, five (all of whom had an autograft including the knee joint surface) had joint deformities, and seven had bone non-union. Conclusion Frozen inactivated autologous tumor bone replantation is safe and results in good bone healing. But this method is not suitable for patients with autograft involving the knee joint surface.